Q. 11 B4.0( 9 Votes )

# Let us write the

Answer :

The given equation is

Given one of the roots is 2.

So, 2 must satisfy the equation.

∴ (2)^{2}-(2 + b) × 2 + 6 = 0

⇒ 4-4-2b + 6 = 0

⇒ -2b = -6

⇒ b =

⇒ b = 3

Therefore, the value of b is 3.

∴ the equation is

⇒

Therefore the other root is 3.

Rate this question :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics